Fast predictive control of linear, time-invariant systems using an algorithm based on the fast gradient method and augmented Lagrange multipliers - Kogel, M.; Findeisen, R. (2011 IEEE International Conference on Control Applications (CCA), 2011)
We present an algorithm based on the fast gradient method and augmented Lagrange multipliers for model predictive control of linear, discrete-time, time-invariant, systems with constraints. In particular, the algorithm solves the underlying quadratic program in the so-called condensed form and takes advantage of the problem structure. At the end, we illustrate the performance of the algorithm, which is competitive with tailored interior-point methods, by an example.